2020
DOI: 10.1002/eji.202048855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of everolimus‐based drug regimens on CMV‐specific T‐cell functionality after renal transplantation: 12‐month ATHENA subcohort‐study results

Abstract: Post‐transplant cytomegalovirus (CMV) infections and increased viral replication are associated with CMV‐specific T‐cell anergy. In the ATHENA‐study, de‐novo everolimus (EVR) with reduced‐exposure tacrolimus (TAC) or cyclosporine (CyA) showed significant benefit in preventing CMV infections in renal transplant recipients as compared to standard TAC + mycophenolic acid (MPA). However, immunomodulatory mechanisms for this effect remain largely unknown. Ninety patients from the ATHENA‐study completing the 12‐mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…of acute lymphocytic choriomeningitis virus infection 26 and the number of CMV-specific T cells in R+ KTRs. [8][9][10][11]27 Our quantiFERON-CMV data indicate that the quantity of gamma-interferon produced by CMV-specific T cells increased rapidly after the initiation of EVR.…”
Section: Discussionmentioning
confidence: 61%
“…of acute lymphocytic choriomeningitis virus infection 26 and the number of CMV-specific T cells in R+ KTRs. [8][9][10][11]27 Our quantiFERON-CMV data indicate that the quantity of gamma-interferon produced by CMV-specific T cells increased rapidly after the initiation of EVR.…”
Section: Discussionmentioning
confidence: 61%
“…Of note, immunosuppressive treatment with mammalian target of rapamycin-inhibitors is superior to calcineurin inhibitor therapy in preventing CMV infection and disease 8 and was shown to be associated with preserved CMV-specific T-cell functionality. 9 In the current study, immunosuppression was already tapered prior to initiation of secondary prophylaxis with letermovir (Figure 1), which may indicate that this had not contributed to the induction of specific immunity in these cases. However, six out of seven patients had also received intravenous immunoglobulins (Figure 1), which may reduce the viral load by passively conferring neutralizing activity towards CMV.…”
mentioning
confidence: 61%
“…Compelling data suggest an antivirial role of mTOR-I by blocking cellular proliferation and impairing pathways critical for infection, signaling, and replication ( Liacini et al, 2010 ; Clippinger et al, 2011 ). In addition, mTOR-I may have a direct anti-viral activity by increasing the percentage of multifunctional virus-specific CD4 T cells ( Hauser et al, 2021 ).…”
Section: Tor-i and The Need To Reduce Dosage In Covid-19 Positive Kidney Transplant Recipientsmentioning
confidence: 99%
“…Several clinical trials have reported a reduced rate of Cytomegalovirus and BKV infections in kidney transplant recipients treated with mTOR-Is alone or associated to low dosages of calcineurin inhibitors (CNI) compared to those in standard dose CNI regimen (Tedesco Silva et al, 2010;Brennan et al, 2011;Mallat et al, 2017;Tedesco-Silva et al, 2019;Hauser et al, 2021). The exact mechanism behind this protection is not clear.…”
Section: Mtor-i and The Need To Reduce Dosage In Covid-19 Positive Kidney Transplant Recipientsmentioning
confidence: 99%